TD-DFT Investigations on Optoelectronic Properties of Fluorescein Dye Derivatives in Dye-Sensitized Solar Cells (DSSCs) - Juma Mzume Juma; Said Ali H. Vuai; N. Surendra Babu (International Journal of Photoenergy, 2019)
This research work was conducted to investigate the structural, molecular, electronic, and photophysical parameters of the fluorescein dye derivatives using the density functional theory (DFT) and time dependent-density functional theory (TD-DFT) computations. The organic donor-π-acceptor dye used for dye-sensitized solar cells, based on 2-(3-hydroxy-6-oxo-6H-xanthene-9-yl)benzoic acid (fluorescein) and its five derivatives, was investigated. The derivatives were formed by attaching different donor groups at para position. The excited state energies, electron absorption spectra, and oscillator strengths (f) were calculated using TD-DFT/B3LYP/6-311G basis set calculations on fully DFT-optimized geometries. The HOMO orbital, LUMO orbital, and energy gap values show that fluorescein attached with thiophene (FST) compound has a smaller energy gap compared to others and the fluorescein attached with an amine (FSA) have a larger energy gap than all compounds. The increasing order of the energy gap between HOMO and LUMO for the fluorescein and its derivatives is FST < FSE < FSM < FS < FSO < FSA. In terms of electron injection efficiency, it was found that the FST has higher electron injection efficiency compared with other derivatives. In addition, light-harvesting efficiencies (LHEs) were calculated and the results showed that the FST has the highest LHE value. It is therefore suggested that FST has better properties for application in DSSC according to the result obtained.